Monocyte and T Cell Immune Phenotypic Profiles Associated With Age Advancement Differ Between People With HIV, Lifestyle-Comparable Controls and Blood Donors - De Francesco, Davide; Sabin, Caroline A.; Reiss, Peter; Kootstra, Neeltje A. (Frontiers in Immunology, 2020)
Motivation People with HIV on successful antiretroviral therapy show signs of premature aging and are reported to have higher rates of age-associated comorbidities. HIV-associated immune dysfunction and inflammation have been suggested to contribute to this age advancement and increased risk of comorbidities. Method Partial least squares regression (PLSR) was used to explore associations between biological age advancement and immunological changes in the T cell and monocyte compartment in people with HIV (n=40), comparable HIV-negative individuals (n=40) participating in the Comorbidity in Relation to AIDS (COBRA) cohort, and blood donors (n=35). Results We observed that age advancement in all three groups combined was associated with a monocyte immune phenotypic profile related to inflammation and a T cell immune phenotypic associated with immune senescence and chronic antigen exposure. Interestingly, a unique monocyte and T cell immune phenotypic profile predictive for age advancement was found within each group. An inflammatory monocyte immune phenotypic profile associated with age advancement in HIV-negative individuals, while the monocyte profile in blood donors and people with HIV was more reflective of loss of function. The T cell immune phenotypic profile in blood donors was related to loss of T cell function, whereas the same set of markers were related to chronic antigen stimulation and immune senescence in HIV-negative individuals. In people with HIV, age advancement was related to changes in the CD4+ T cell compartment and more reflective of immune recovery after cART treatment. Impact The identified monocyte and T cell immune phenotypic profiles that were associated with age advancement, were strongly related to inflammation, chronic antigen exposure and immune senescence. While the monocyte and T cell immune phenotypic profile within the HIV-negative individuals reflected those observed in the combined three groups, a distinct profile related to immune dysfunction, was observed within blood donors and people with HIV. These data suggest that varying exposures to lifestyle and infection-related factors may be associated with specific changes in the innate and adaptive immune system, that all contribute to age advancement.